2017
DOI: 10.1108/aa-09-2016-121
|View full text |Cite
|
Sign up to set email alerts
|

Key assembly structure identification in complex mechanical assembly based on multi-source information

Abstract: Purpose The purpose of this paper is to find a method for key assembly structure identification in complex mechanical assembly. Three-dimensional model reuse plays an increasingly important role in complex product design and innovative design. Assembly model has become important resource of models reuse in enterprises, which contains certain function assembly structures. These assembly structures implicating plenty of design intent and design experience knowledge can be used to support function-structure desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
(18 reference statements)
0
14
0
Order By: Relevance
“…The common design structure appears frequently in many assembly models and is equipped with certain functions. Han et al (2017) identified key function part and key assembly structure in complex assembly model by considering assembly topology and multi-source attributes information, where complex network is used to evaluate importance of assembled parts. The common design structure and key assembly structure are very significant design structure information for assembly model in model repository, which should be labeled with some functional semantics.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The common design structure appears frequently in many assembly models and is equipped with certain functions. Han et al (2017) identified key function part and key assembly structure in complex assembly model by considering assembly topology and multi-source attributes information, where complex network is used to evaluate importance of assembled parts. The common design structure and key assembly structure are very significant design structure information for assembly model in model repository, which should be labeled with some functional semantics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Where, P is a set of nodes representing assembled parts, L is a set of edges representing connection relationships between parts, A(P) is a set of attributes of the nodes containing mainly multiple attributes of parts, and A(L) is a set of attributes of the edges containing at least assembly features and assembly constraints information. To analyze conveniently structurefunction for CAD assembly model, assembled parts are classified into two categories: connector and function part (Han et al, 2017). An example of mechanical CAD assembly is shown in Figure 4.…”
Section: Structure-function Correlations Analysis and Functional Semantic Annotationmentioning
confidence: 99%
“…Taking the geared oil pump shown in Fig.1 as an example. According to the method proposed by Han et al (2017Han et al ( ,2018, the key functional parts are selected according to the comprehensive importance of the parts topological information and the multi-source attribute information. The former includes degree, density, and number of parts.…”
Section: Recognition Of Key Functional Partsmentioning
confidence: 99%
“…According to the identification method proposed by Han et al(2017), assembly model is represented based on complex network, which is map to an attributed adjacency graph. Extracting and computing the topological information (degree centrality, closeness centrality and betweenness centrality) and multi-source attributes of parts, taking use of a two-level evaluation model to evaluate importance of parts assembled, and the key function parts in assembly can be obtained by sorting result.…”
Section: The Descriptor Of Assembly Modelmentioning
confidence: 99%
See 1 more Smart Citation